Incidence and risk factors of surgical site infection in prolapsed lumbar intervertebral disc surgery - Adhikari, Shirish; Paudel, Sushil; Kafle, Dinesh; Pokharel, Rohit Kumar (Nepal Orthopaedic Association Journal, 2020)
INTRODUCTION: Discectomy for prolapsed intervertebral disc is commonly done spine surgery and has a risk of Surgical Site Infection that leads to higher morbidity and healthcare costs. To develop strategies to reduce the risk for Surgical Site Infection, independent risk factors for it should be identified. We report incidence and risk factors for post-operative Surgical Site Infection among the cases operated in a tertiary level referral hospital. METHODS: A prospective analytical study was carried on forty-six lumbar prolapsed intervertebral disc patients who met the inclusion criteria and were included in the study. Preoperative, peroperative, and postoperative risk factors of individual patients were gathered in a Performa. Patients were divided into two groups: with Surgical Site Infection and without Surgical Site Infection. Risk factors were analyzed between two groups. RESULTS: There were 6 cases of postoperative Surgical Site Infection with an incidence of 13.04%; 3 deep infection and 3 superficial. Independent risk factors like Age (p<0.073), Sex (p<1.00), Hemoglobin (p<0.794), Alcohol use (p<0.831), Smoking (p<0.305), Preoperative Random Blood Sugar (p<0.282), Total leukocyte count (p<0.232), Albumin level (p<0.628), Body Mass Index (p<0.604), Duration of Surgery (p<0.913), Type of surgery and Type of postoperative bed were not found to be significant risk factors. CONCLUSION: The overall incidence of Surgical Site Infection in lumbar Prolapsed intervertebral disc surgery is higher in our setting but we could not identify any independent risk factors. Unknown intra-operative factors that we did not include in the study seem to be the risk factors.